Solid medications administered via feeding tube: scoping review - Pires Junior, Elson de Barros; Gemaque, Henrique Eron da Silva; Leite, Soany Soares; Carneiro, Alexandre Mansuê Ferreira; Soler, Orenzio; Arruda, José Eduardo Gomes (Revista JRG de Estudos Acadêmicos, 2024)
The objective was to map protocols for administering solid medications via nasoenteral and na-sogastric tubes. As a method, a scoping review was conducted, applying the PRISMA-ScR: Exten-sion for Scoping protocol, with a time frame from 2018 to 2023. In addition to scientific databases such as Lilacs, Pubmed, Scielo, and JBI, Google Scholar and repositories of Higher Education In-stitutions were also used to access grey literature. As a result, 17 scientific papers were selected. It is recognized, finally, that there is a high frequency of errors in the administration of solid med-ications via tube, whether enteral or nasoenteral, which can lead to losses in drug bioavailability and compromise good practices in drug therapy. In this context, the presence of a clinical phar-macist is essential, particularly for implementing evidence-based practices, with a view to care quality, patient safety, service efficiency, and sustainability.